Risk indicators for dental caries using the International Caries Detection and Assessment System (ICDAS) - Ismail AI, Sohn W, Tellez M, Willem JM, Betz J, Lepkowski J (Blackwell Synergy, 2008)
While national surveys have found that African– Americans have a higher prevalence and severity of dental caries than white- Americans, there are only a few descriptive studies of the prevalence and severity of dental caries in low-income urban African–Americans.